Who, where and why? Characterizing China's rural population and residual rural poverty. Issue 1 (2nd January 2020) - Dunford, Michael; Gao, Boyang; Li, Wenbin
ABSTRACT: China is noted for remarkable reductions in rural poverty and aims to eliminate it by 2020. Achieving this outcome requires identification of the remaining poverty population and a strategy that effectively addresses the causes of their poverty. Drawing on a 2017 survey of 4626 rural households and 13, 689 individuals in 628 counties, characteristics of rural China, of people identified as remaining poor and of poverty classifications, are examined, enabling an assessment of the general effectiveness of poverty targeting. Analysis of the causes of remaining rural poverty indicates the need for a combination of targeted development-oriented policy for poverty counties, villages and regions, and minimum life guarantees and public service measures for poverty households.